Pengaruh Latar Belakang Pendidikan Direksi dan Struktur Kepemilikan terhadap Pengungkapan Keberlanjutan pada Perusahaan Agrikultur Indonesia: Peran Hilirisasi dan Sertifikasi sebagai Variabel Moderasi - Suhardjo, Iwan; Meiliana, Meiliana; Fransiska, Fransiska; Lee, Angelica; Gary, Gary (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of the educational background of the board of directors and ownership structure, as well as downstreaming and certification as a moderation of sustainability disclosure in agricultural companies in Indonesia. Sustainability Disclosure is the process of providing information regarding a company's commitment to social, environmental and economic aspects. The research method used is quantitative by collecting data from the financial reports of agricultural sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The number of companies used was 10 agricultural companies. This research contributes to the literature on corporate sustainability, especially in the agricultural sector, by broadening understanding of the factors that significantly influence sustainability disclosure, namely ownership structure and certification can weaken the relationship between board of directors' educational background and sustainability disclosure.